A COMPARATIVE STUDY OF PREDICTIVE SUPERVISED-MACHINE LEARNING ALGORITHMS ON CARDIOVASCULAR DISEASES (CVD) - Alina Faisal; Dr. Syed E. Ahmed; Mahnaz Makhdum; Dr. Farah Naz Makhdum (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Supervised machine learning (S-ML) applications in the medical niche assist in attenuating the fatality rates as it is an arduous challenge for cardiologists to predict the patterns from the clinical data. The objective of this comparative research study is to determine the best S-ML algorithm amongst the full model, submodel I and II for the prediction of the incidence of death events due to heart failure. S-ML classification algorithms including logistic regression, ridge classifier, random forest, decision tree, and SVM with and without hyperparameter tuning using GridSearch CV were applied to a Kaggle dataset for extensive performance analysis. Feature importance techniques including random forest feature selection, and SHAP approach using the XGBoost library were used to create two submodels. The conclusion drawn from the predicted results suggested decision tree as the best algorithm due to its highest accuracy (78%, 77%, 74%) and least root-mean-square error (RMSE) (0.471, 0.483, 0.506) among the S-ML algorithms implemented on all the models. To the best of our knowledge, the implementation of linear and James-Stein shrinkage estimator strategies is the first empirical analysis of a CVD dataset. It showed submodel II as the best fit, and BIC scores showed submodel I as a better-performing model.